Endobronchial ultrasound learning curve in interventional pulmonary fellows. Issue 2 (9th December 2014) - Stather, David R.; Chee, Alex; MacEachern, Paul; Dumoulin, Elaine; Hergott, Christopher A.; Gelberg, Jacob; Folch, Eric; Majid, Adnan; Gonzalez, Anne V.; Tremblay, Alain
Abstract Background and objective Little published data exist regarding the learning curve for endobronchial ultrasound‐transbronchial needle aspiration (EBUS‐TBNA). We sought to assess the improvement in skill as trainees learned EBUS‐TBNA in a clinical setting. Methods This is a multicentre cohort study of EBUS‐TBNA technical skill of interventional pulmonology (IP) fellows as assessed with EBUS‐TBNA computer simulator testing every 25 clinical cases throughout IP fellowship training. Results Nine fellows from three academic centres in the United States and Canada were enrolled in the study. Ongoing improvements were seen for EBUS‐TBNA efficiency score and percentage of lymph nodes correctly identified on ultrasound exam, even after 200 clinical cases. Expert‐level technical skill was obtained for EBUS efficiency score and for percentage of lymph nodes correctly identified on ultrasound exam at a median of 212 and 164 procedures, respectively; however, 33% of fellows did not achieve expert‐level technical skill for either metric during their fellowship training. Significant variation in learning curves of the fellows was observed. Conclusions Significant variation is seen in the EBUS‐TBNA learning curves of individual IP fellows and for individual procedure components, with ongoing improvement in EBUS‐TBNA skill even after 200 clinical cases. These results highlight the need for validated, objective measures of individual competence, and can assist training programmes in ensuring adequate procedure volumes required for a majority of trainees to successfully complete these assessments.